Infraestructura cafetera para la mujer rural. Complejo agroturístico, núcleo de desarrollo asociativo entre mujeres La Plata - Huila (2021)
The department of Huila has established itself as the main exponent in the coffee sector due to the significant rate of production, before the incessant growth the need for free spaces for the development of coffee knowledge among rural women is evidenced that allow through associative work to establish necessary sustenance and that the product is not overvalued, prevailing the standards of quality and excellence focused on coffee families headed by rural women who are the fundamental pillar in the affiliate nucleus. The deficit of spaces gives way to the loss of the coffee tradition focused on migration from the countryside to the city due to lack of income and support in the Huila countryside, it is a priority to serve rural communities in crisis, emphasizing direct marketing through cooperatives farmers, establish organic production methods avoiding water damage to the ecosystem in which the coffee plantation is located due to its important tributaries, sale of coffee under fair market conditions and finally achieve a diversified production that allows the development of the internal market.